2015
DOI: 10.3917/mond1.152.0045
|View full text |Cite
|
Sign up to set email alerts
|

« Le Chili est proche »

Abstract: En 1974, l’Unité populaire et le coup d’État chiliens ont une importance particulière dans la transition démocratique grecque et la légalisation de la gauche communiste, bannie depuis 1936. Cet article analyse les processus politiques et culturels des années 1967-1974 – en particulier, l’essor de la pensée tiers-mondiste et du guévarisme –, qui conduisent à l’adoption de l’Unité populaire comme référence centrale du mouvement antidictatorial grec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After the overthrow of President Allende in Chile in September 1973, campaigns over Greece became closely interrelated with solidarity campaigns on behalf of the Chilean opposition. 136 Chilean exiles were keen to link their fight against fascism in Chile with the plight of Southern Europe. When the Chilean Communist Party leader Volodia Teitelboim addressed the audience of an international Helsinki conference on Chile staged by the World Peace Council in September 1973, he declared his country to be another Greece, and blamed the United States for being the common orchestrator of fascist regimes overthrowing democracy.…”
Section: The Failure Of An Anti-totalitarian Struggle In the 1970smentioning
confidence: 99%
“…After the overthrow of President Allende in Chile in September 1973, campaigns over Greece became closely interrelated with solidarity campaigns on behalf of the Chilean opposition. 136 Chilean exiles were keen to link their fight against fascism in Chile with the plight of Southern Europe. When the Chilean Communist Party leader Volodia Teitelboim addressed the audience of an international Helsinki conference on Chile staged by the World Peace Council in September 1973, he declared his country to be another Greece, and blamed the United States for being the common orchestrator of fascist regimes overthrowing democracy.…”
Section: The Failure Of An Anti-totalitarian Struggle In the 1970smentioning
confidence: 99%
“…Recent research, for instance, has revealed how the Greek left's interest in the Third World was mediated through Eastern European governments and Greek communists in exile, who translated documents and texts from Spanish and other foreign languages into Greek. 90 Likewise, as Christiaens argues, Portuguese, Greek and Spanish communists made contact with anti-colonial movements at the level of international communist organisations, such as the World Peace Council and the World Federation of Trade Unions. In the early 1980s Spanish Christian democrats helped the fledging Polish trade union Solidarność to reach out to the Southern cone, whilst Spanish firms helped Hungarian enterprises, through joint ventures, to crack the Latin American market.…”
Section: East-south Détente the 'Third World' And Alternative Europementioning
confidence: 99%